20.8k views
4 votes
20 points! Thank you :)

20 points! Thank you :)-example-1

2 Answers

5 votes

The quadratic expression:


2 {x}^(2) - 2x - 12

★ By split middle term,we get


2 {x}^(2) - 6x + 4x - 12


2x(x - 3) + 4( x - 3)


(2x + 4) (x - 3)


2x + 4 = 0 \: \: and \: \: x - 3 = 0


2 x = - 4 \: \: and \: \: x = 3


x = - 2 \: \: and \: \: x = 3

Therefore , the two solution of given quadratic equations is -2 and 3.

User Mark Sands
by
5.0k points
6 votes

Answer:


\Large \boxed{x=-2 \ \mathrm{and} \ x=3}

Explanation:

The quadratic expression is given.


2x^2-2x-12=0

Factor the left side of the equation.


2(x+2)(x-3)=0

Set the factors equal to 0.


x+2=0


x=-2


x-3=0


x=3

The two solutions work in the original equation. The solutions make the equation true.

User Bleadof
by
5.2k points